World port cities as cosmopolitan risk community: Mapping urban climate policy experiments in Europe and East Asia. (June 2016) - Blok, Anders; Tschötschel, Robin
Extending Ulrich Beck's theory of world risk society, this article traces the emergence of a cosmopolitan risk community of world port cities in Europe and East Asia, constituted around shared imaginations of the global risks and opportunities of climate change. Such urban risk imaginations are shaped and circulated, we argue, within transnational assemblages of local government networks, international organizations, multinational insurance companies and transnational non-governmental organizations. Adopting the methodology of mapping urban climate experiments, we then document one policy indication of this cosmopolitan risk community, in terms of the timing, intensity, priorities and modes of government manifested in the climate policy engagements of 16 major world port cities across the regions of Europe and East Asia. The substantial similarities in such policy engagements, we conclude, amount to a new urban–cosmopolitan realism, reshaping urban politics in the face of climate change.